2015
DOI: 10.1038/nn.4026
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent DNA methylation regulates plasticity in the developing visual cortex

Abstract: DNA methylation is an epigenetic repressor mark for transcription dynamically regulated in neurons. We analyzed visual experience regulation of DNA methylation in mice and its involvement in ocular dominance plasticity of the developing visual cortex. Monocular deprivation modulated the expression of factors controlling DNA methylation and exerted opposite effects on DNA methylation and hydroxymethylation in specific plasticity genes. Inhibition of DNA methyltrasferase (DNMT) blocked molecular and functional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…We chose to study brain because it has abundant mitochondria (47) and because epigenetic modifications in brain tissues have already been implicated in modulating transcriptional changes that are important for synaptic connections and circuitry rewiring (28, 48). Our studies were performed using cerebella harvested at eight weeks of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to study brain because it has abundant mitochondria (47) and because epigenetic modifications in brain tissues have already been implicated in modulating transcriptional changes that are important for synaptic connections and circuitry rewiring (28, 48). Our studies were performed using cerebella harvested at eight weeks of age.…”
Section: Resultsmentioning
confidence: 99%
“…This covalent modification is usually found at cytosine residues within CpG dinucleotides and is catalyzed by DNA methyltransferase (DNMT). In most human tissues, the vast majority of the genome is highly methylated (>70%), including at repetitive sequences (26, 28), gene bodies (26, 29, 30) and other regulatory regions. Most often methylation occurs within CpG dinucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…We show that these changes are paralleled by a considerable transcriptome rearrangement: many miRNAs undergo a remarkable change of expression between P10 and P28 with the top hits being miR-29, that was previously involved in regulating epigenetic enzymes important for cortical plasticity6; miR-338 and miR-219, that were suggested to be key players in myelination4243; and miR-132/212, a miRNA family previously involved in synaptic plasticity8910112644454647. The combined analysis of miRNAs and mRNAs in the visual cortex of wt and miR-132/212 null mice revealed that genes downregulated with age and upregulated by miR-132/212 deletion are highly enriched with miR-132-3p targets and, to a much lesser extent, with targets of miR-212-5p, the only two members of the miR-132 family abundantly expressed in the visual cortex.…”
Section: Discussionmentioning
confidence: 96%
“…At cerebral level, miRNAs have been mainly studied during early phases of development2 or in models of neuropathological disease3 and neural plasticity4567. Recent evidence has demonstrated that visual experience is able to influence cortical levels of specific miRNAs89 and that tight regulation of miR-132 levels is required for ocular dominance (OD) plasticity during a sensitive period of development891011. However, neither miR-132 nor other miRNAs have ever been investigated in the context of physiological maturation of cortical functions.…”
mentioning
confidence: 99%
“…For example, sensory input can dynamically regulate both 5mCG and 5hmC in the primary visual cortex of young but not adult mice. Inhibition of DNMTs blocked the negative functional impact of sensory deprivation, suggesting that dynamic DNA methylation changes modulate the experience-dependent transcription that is necessary for sensory input to correctly sculpt the developing visual system 72 . Additional work supports the role of active DNA methylation and demethylation in regulating experience-dependent plasticity and brain processes in adulthood (BOX 2).…”
Section: Dna Methylation Across Brain Developmentmentioning
confidence: 96%